2019
DOI: 10.1039/c9em00111e
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating the dark side of indoor oxidants

Abstract: A review of the current understanding of oxidants and their precursors in indoor environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 93 publications
0
85
0
Order By: Relevance
“…The oxidative capacity has been significantly less explored in indoor environments. However, recent studies in atmospheric science have started looking at indoor oxidants and their precursors, in which the combination of indoor oxidants and their precursors will be referred to as "oxidants*" [117]. It has been supposed that ozone (O 3 ), the hydroxyl radical (OH), and the nitrate radical (NO 3 ) are major oxidants* [118].…”
Section: The Oxidative Capacity Of Indoor Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidative capacity has been significantly less explored in indoor environments. However, recent studies in atmospheric science have started looking at indoor oxidants and their precursors, in which the combination of indoor oxidants and their precursors will be referred to as "oxidants*" [117]. It has been supposed that ozone (O 3 ), the hydroxyl radical (OH), and the nitrate radical (NO 3 ) are major oxidants* [118].…”
Section: The Oxidative Capacity Of Indoor Environmentmentioning
confidence: 99%
“…Oxidation is regarded as the dominant process in ozone reactions indoors; thus, most research into indoor oxidants* has focused solely on ozone. Recently, it was demonstrated that the formation of OH radicals by formaldehyde (HCHO) and photolysis of nitrous acid (HONO) is an important source of indoor oxidants* (Figure 1) [117]. In the atmosphere, the OH radical is known as the key species in photo-oxidation cycles; it can oxidize VOCs to form secondary aerosols or other gas species, which can cause toxic and carcinogenic effects in humans [119].…”
Section: The Oxidative Capacity Of Indoor Environmentmentioning
confidence: 99%
“…With low light levels indoors, the rate of oxidant production in indoor environments is generally much smaller than outdoors. 65 Ozone is viewed as the major gas-phase oxidant in indoor environments, transported inside aer being photochemically generated in the outdoor troposphere. [65][66][67][68] Indoor mixing ratios are typically 0.1 to 0.8 of outdoor mixing ratios, with lower values observed in less well-ventilated spaces.…”
Section: Indoor Oxidantsmentioning
confidence: 99%
“…65 Ozone is viewed as the major gas-phase oxidant in indoor environments, transported inside aer being photochemically generated in the outdoor troposphere. [65][66][67][68] Indoor mixing ratios are typically 0.1 to 0.8 of outdoor mixing ratios, with lower values observed in less well-ventilated spaces. 67,69 The fraction of outdoor ambient ozone that makes its way through walls and windows (i.e.…”
Section: Indoor Oxidantsmentioning
confidence: 99%
“…[47], in addition, a study displayed that indoor VOCs level had increased significantly after burning essential oils [48]. O 3 was one of the indoor oxidants [49,50], and Waring et al demonstrated that 68% of all O 3 reactions were with D-limonene, and 26% of all O 3 reactions are with α-pinene [50]. This might be the reason why the essential oil use could decrease the O 3 level.…”
Section: Discussionmentioning
confidence: 99%